D’un mythe l’autre ou l’intertexte à l’oeuvre dans Le Jour des corneilles de Jean-François Beauchemin - Piccione, Marie-Lyne (Romanica Silesiana)
Patricide in Jean-Francois Beauchemin’s “Le jour des corneilles” is interpreted as a pretext to invoke classical myths and texts (Camus’s “The Stranger”, Homer’s “Oddyssey”). The author examines the parallels between the sufferings of an abused son, presented as a new Orpheus, and the emblematic figures of Sisyphus and Prometeus. Key words: classical myths; rewriting; Jean-Francois Beauchemin